Erratum Jurnal Psikologi Volume 25 Number 1, 1998 - Erratum Jurnal Psikologi (Faculty of Psychology, Universitas Gadjah Mada, 2022)
This erratum is to explain a pagination error occurred in the published issue of Jurnal Psikologi Volume 25, Number 1 (1998). The error above was due to problem in scanning the printed version of the article that caused one needless page slipped between page 18 and 19. The error only applies on the PDF files of the articles, but the metadata remains the correct page.